Deadly justice without mercy in East Asia?. Issue 2 (3rd April 2022) - Pascoe, Daniel; Novak, Andrew
ABSTRACT: This article explores executive clemency in death penalty cases in China, Taiwan and Japan. All three neighbouring legal jurisdictions are notable for frequently passing death sentences and executing prisoners over the past several decades without the executive branch of government granting individualised pardon or commutation to any death row prisoner since at least 1975, if not earlier. This highly unusual feature of all three nations' death penalty practice suggests a policy puzzle. The authors' case study comparison of these three East Asian jurisdictions reveals two common explanatory features. First is the availability of alternative post-appellate procedures to mitigate punishment in cases undeserving of death, and to limit execution totals for policy reasons. Second is the inability of condemned prisoners to directly access the ultimate clemency decision-maker by petition, unlike in most death penalty retentionist jurisdictions. The authors conclude by making several policy recommendations on this basis.